Trazodone for the treatment of sleep disorders in dementia: an open-label, observational and review study - Camargos,Einstein Francisco (2011)
Sleep disorders (SD) in patients with dementia are very common in clinical practice. The use of antidepressants with hypnotic actions, such as trazodone, plays an important role in these cases. The aim of this study is to present a profile of the use of trazodone in demented patients with SD, as well as a review of trazodone hydrochloride in SD. We evaluated 178 elderly patients with Alzheimer's disease and other dementias, clinically presenting SD and treated with hypnosedative medications. In the one-year period comprising the study, 68 (38.2%) of the 178 had sleep disorders. Most patients (114; 64%) had a diagnosis of Alzheimer's disease. Approximately 85% of patients with SD used hypnosedative drugs. Trazodone was the most commonly used drug among patients (N = 35), with an effectiveness of 65.7%. Trazodone has been shown to be a good option for treatment of the elderly with dementia and associated SD.